JUSTIFICATION OF RATIONAL OPERATING PARAMETERS OF VIBRATION DISC-WORKING ENGINES OF SEEDING UNITS TO IMPROVE ENERGY-TECHNOLOGICAL INDICATORS - Guryanov, Georgy; Doudkin , Mikhail; Kim, Alina; Vavilov, Andrey; Asangaliev, Yelibek; Yakovlev, Vladimir; Vasilyeva, Olga; Vavilov, Oleg (Journal of Applied Engineering Science, 2024)
The article addresses the interaction of disc vibration working elements of a seed drill with soil to reduce traction resistance and energy consumption in soil processing. Regularities characterizing the impact of vibrations on the soil are identified, and a mechanical-mathematical model of soil cutting by the vibrational disc-working element of a seed drill is developed. Mathematical dependencies for determining the parameters of vibro-impact interaction of the cutting edge of the disc-working element with the soil are obtained. The efficiency conditions of the vibro-cutting process, in terms of reducing traction resistance and energy consumption, are established. A methodology for selecting rational parameters for vibro-cutting soil in the design and operation of the disc-working element of seeding equipment is developed. Experimental results of a prototype vibrational working equipment are presented, confirming theoretical findings and demonstrating the effectiveness and feasibility of vibrational soil cutting by the disc-working element for reducing traction resistance and energy costs. The research, the results of which are presented in this article, is funded by the Committee on Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan (grant AP14869252 "Development of the universal sowing complex with increased productivity for the agro-industrial production of the Republic of Kazakhstan").